α-klotho reduces susceptibility to osteoarthritis: evidence from cross-sectional studies and Mendelian randomization - Li, Zhao; Li, Zhong; Cheng, Qisheng; Nie, Xinlin; Cui, Yu; Du, Bing; Ren, Taotao; Xu, Yibo; Ma, Teng (Frontiers in Endocrinology, 2024)
Background Despite extensive research, the association between serum α-klotho levels and osteoarthritis (OA) remains unclear, predominantly relying on findings from OA mouse models. This study used data from the National Health and Nutrition Examination Survey (NHANES) to conduct a cross-sectional study examining the relationship between α-klotho and human OA. In addition, we used Mendelian randomization (MR) to genetically infer a causal relationship between serum α-klotho and the three OA subtypes. Method A cohort of 12,037 subjects from NHANES (2007-2016) was analyzed. Multivariate logistic regression was utilized to examine the association between α-klotho concentration and OA, alongside subgroup analysis and interaction tests. Additionally, a two-sample bi-directional MR analysis was conducted to evaluate the relationship between serum α-klotho and three OA subtypes, including all OA, hip OA, and knee OA, employing the inverse variance weighting (IVW) method as the primary approach. Results Following adjustment for covariates, a nonlinear negative correlation between serum α-klotho and OA was observed (OR=0.77; 95% CI, 0.68-0.88, p < 0.0001). The IVW method revealed that higher serum α-klotho levels were associated with decreased susceptibility to hip OA (OR = 0.92, 95% CI: 0.87–0.98, P = 9.64×10-3). However, MR analysis did not establish a causal relationship between serum α-klotho and OA or knee OA. Inverse MR also indicated that the three subtypes of OA do not causally affect serum α-klotho concentrations. Conclusions In cross-sectional studies, α-klotho showed a nonlinear negative correlation with OA. MR analysis of outcomes was not identical to cross-sectional studies.